Phytochemical Screening and Antiproliferative Potential of Some Medicinal Plants in Northeastern Nigeria (Journal of Environmental Bioremediation and Toxicology, 2023)
The use of medicinal plants for the therapy of different disease conditions has been in practice for decades, this has been attributed to the various phytoconstituents present in plants.  This study seeks to investigate the presence of secondary metabolites and assess the growth inhibitory properties of the plant extracts Curcuma longa, Momordica balsamia, Prosopis africana, Zizipus mauritianai, Boswellia dalziel, Guiera senegalensis and Diospyros mespiliformis. The method used to assess the growth inhibitory potential of the extracts involved the incubation of viable Sorghum bicolor seed in different concentrations of the extracts and water as a control. The seeds radicle lengths were measured at different time intervals to ascertain the antiproliferative activity of the extracts. The results showed the presence of alkaloids, coumarins, flavonoids, phenolics, steroids, terpenoids, tannins, saponins, quinone, anthraquinone and glycosides. The antiproliferative potential of the plants was evident by the concentration-dependent decrease in the growth of the seeds in the different extracts. This suggests that when explored further; extracts from the different plants might be used as potential antitumor and anticancer agents.
Keywords: Antiproliferative; Phytoconstituents; Sorghum bicolor seed; Inhibition; Anticancer